Trends in rates of Gram-negative Bloodstream Infections (BSI) and Fluoroquinolone (FQ) resistance in Allogeneic Hematopoietic Cell Transplant (HCT) Recipients at Memorial Sloan Kettering Cancer Center (MSK) during 2012–2016. (4th October 2017) - Chan, Shuk-Ying; Chung, Dick; Cheteyan, Leslie A; Seo, Susan; Papanicolaou, Genovefa
Abstract: Background: Over the last decade, FQ prophylaxis (ppx) is used broadly for BSI prevention post HCT. Increasing rates of Gram-negative (GN) BSI and rising antibiotic resistance (R) have been recently reported. Since 2006, we have used FQ and Vancomycin (VAN) ppx at our center. We have reported low rates of GN BSI rates and FQ R during 2006–2011. In this study, we report the epidemiology of BSI during 2012–2016 focusing on FQ R among GN Bacteria (GNB). Methods: Observational study of 872 adult recipients of first HCT from 1/1/2012 to 12/31/2016 at MSK. BSI was defined as ≥1 positive blood culture from day(D) -2 to D100. Early period (EP) (D-2 to 30) and Late period (LP) (D>30–100) BSI were compared. FQ and VAN was ppx started on D-2 until neutrophil engraftment or empiric treatment for fever and neutropenia (F&N), whichever came first. Piperacillin/tazobactam (P/T) was first line therapy for F&N; cefepime (CPM) was used as alternative. Results: Of 872 patients, 76.5% received peripheral blood, 16.5% received cord and 7% received marrow allografts from matched related (27%), matched unrelated (42.4%), haploidentical (2.6%) or mismatched (28%) donors after myeloablative (48%), reduced intensity (44.3%) and nonablative (7.7%) conditioning. Overall 174 (20%) patients developed BSI by D100, for a total 214 episodes with 240 isolates comprised of 100 (41.7%) Gram-positive bacteria and 140 (58.3%) GNB. Of 214 BSI episodes, 137 (64%) occurred in the EP. In EP, 66 (7.6%) patients developed GN BSI at a median 6 days (range 4–9) post HCT. Rates were similar by year of study, across stem cell source and conditioning regimens. Escherichia coli ( E coli ) comprised 56.6 % of total GNB. In LP, 42 (4.8%) patients had GN BSI, with Klebsiella spp comprising 34.4% of total GNB (Table 1). Rates of FQ R and P/T R, extended spectrum β-lactamase (ESBL) and multidrug-resistance (MDR, defined as resistance to ≥ 2 of the following: FQ, CPM, P/T or carbapenems (CAR)) among Enterobacteriaceae were higher in EP compared with LP ( P < 0.05) (Figure 1). Conclusion: 1) Rates of early GN BSI remain low (7.6%) after 10 years of FQ ppx. 2) In the EP 80% Enterobacteriaceae were FQ R. Rates of Enterobacteriaceae FQ R, ESBL and MDR GNB were higher in EP compared with LP. CAR R remains low (≤7%) in both periods. Disclosures: All authors: No reported disclosures.